(untitled) (Journal of Applied Learning and Teaching, 2021)
The COVID-19 pandemic has altered the landscape of higher education, forcing institutes across the globe to lock down campuses and shift instructional methods. To determine the impact of these changes on students, 644 currently enrolled higher education students across seven countries (USA, the Netherlands, Ireland, South Korea, China, Malaysia, and Taiwan) were asked to report their pandemic-related concerns. Qualitative responses were translated and indexed by theme, with students reporting major concerns in the areas of education, safety, mental health, employment stability/finances, future, and relationships. Minor themes of travel/getting out, politics, economy, and misinformation were also reported. The results of this study provide broadly endorsed international information on student needs for support and continuity of learning. These findings can be used by institutes of higher education to inform policy and procedure, including but not limited to mental health and risk communication, during the present pandemic and future emergency or disaster situations.